Find out the value of x and y xy=6 2x-y=3 ???
Thanks in advance !
Thanks in advance !
1 Answer
Oct 12, 2017
If would use substitution. If we rearrange the second equation for
2x - 3 = y
Accordingly:
x(2x -3) = 6
2x^2 - 3x - 6 =0
By the quadratic formula, we get:
x = (-(-3) +- sqrt(3^2 - 4 * 2 * -6))/(2 * 2)
x= (3 +-sqrt(57))/4
We can now solve for
y = 2((3 + sqrt(57))/4) - 3
y = (3 + sqrt(57) - 6)/2
y = (sqrt(57) - 3)/2
Now for the other solution, we get:
y = (-sqrt(57) - 3)/2
So our solutions are
Hopefully this helps!